Colour stability and water-holding capacity of M. longissimus and carcass characteristics in fallow deer (Dama dama) grazed on natural pasture or fed barley - Wiklund, Eva; Hutchison, C.; Flesch, J.; Mulley, R.; Littlejohn, R. P. (Rangifer, 2005)
The effects of feeding regimen on carcass characteristics, meat colour and water-holding capacity of M. longissimus were studied in 24 female fallow deer (Dama dama). All animals were farm raised; twelve were grazed on pasture and twelve were fed barley and a small amount of hay prior to slaughter. The animals were slaughtered at two occasions (during the Southern Hemisphere spring); after 19 weeks of feeding (n=12; 6 grazing and 6 barley fed animals; group 1) and after 24 weeks of feeding (n=12; 6 grazing and 6 barley fed animals; group 2). The barley/hay-fed deer had significantly higher body condition scores and carcass weights than the pasture raised group. No difference in meat ultimate pH values between the treatment groups was recorded. The meat from the pasture raised deer had significantly longer colour display life after 2 and 3 weeks of refrigerated storage (+ 2.0 ºC) in vacuum bags. There was no difference in drip loss between the two treatment groups. However, significantly lower drip losses were found in meat from the animals in group 2 compared with the ones in group 1 (P ≤ 0.001). It was concluded that the feeding regimen of the animals is an important factor that contributes to the variation in quality of fresh chilled deer meat (venison), mainly the colour stability and display life of vacuum packaged meat.Abstract in Swedish / Sammanfattning: I denna undersökning ingick 24 dovhjortshindar (Dama dama) för att studera effekterna av olika typer av foder (bete och korn) på slaktkroppskvalitet samt färg och vattenhållande förmåga i köttet (M. longissimus). Alla djur var uppfödda på en hjortfarm, 12 betade gräs och 12 utfodrades med korn och en liten mängd hö före slakt. Djuren slaktades vid två olika tillfällen (under våren på det södra halvklotet); efter 19 veckors utfodring (n=12; 6 betesdjur och 6 kornfodrade djur; grupp 1) och efter 24 veckors utfodring (n=12; 6 betesdjur och 6 kornfodrade djur; grupp 2). De dovhjortar som utfodrats med korn och hö var i bättre kondition och hade högre slaktvikter jämfört med de djur som betat gräs. Ingen skillnad i köttets pH-värde mellan de två utfodringsgrupperna kunde dock påvisas. Köttet från de betande dovhjortarna hade bättre färgstabilitet efter lagring i 2 och 3 veckor (+ 2.0 ºC) i vakuumförpackning. Det fanns ingen skillnad mellan kött från betande och korn/hö-utfodrade djur i vattenhållande förmåga. Däremot hade kött från djur i grupp 2 (slaktade efter 24 veckors utfodring) bättre vattenhållande förmåga jämfört med grupp 1 (P ≤ 0.001). Vi kunde konstatera att de olika fodertyperna påverkade kvaliteten hos färskt kyllagrat kött, framförallt färgstabiliteten hos vakuumförpackat kött.